Well shaped ST segment and risk of cardiovascular mortality. Issue 6823 (8th February 1992) - Schouten, E. G.; Dekker, J. M.; Pool, J.; Kok, F. J.; Simoons, M. L.
Abstract : OBJECTIVE–To investigate the prognostic value of frequently occurring slight variations in the ST segment for cardiovascular mortality in healthy subjects. DESIGN–Follow up study of mortality in relation to variations in ST segment level in a cohort over the 28 years from 1953 to 1981. A case-cohort sampling design was applied to limit the number of electrocardiograms that had to be coded by hand. SETTING–General health examination carried out in 1953 of civil servants in Amsterdam and assessment of subsequent mortality. SUBJECTS–Apparently healthy civil servants aged 40 to 65 years: 1583 men and 1508 women. MAIN OUTCOME MEASURES–Relative risk of variations in ST segment level for mortality from all causes, cardiovascular disease, and coronary heart disease. RESULTS–In men the multivariate relative risks of 15 year mortality from cardiovascular disease and coronary heart disease of slight ST elevation at 80 ms past the J point (compared with isoelectric ST segment) were 0.5 (95% confidence interval 0.3 to 0.9) and 0.4 (0.2 to 0.8), respectively. As expected, ST segment depression (greater than 0.25 mm) was associated with increased risk: 1.9 (1.1 to 3.0) and 2.2 (1.2 to 3.9), respectively. In women associations were weaker. The full 28 year period showed a similar pattern of somewhat weaker associations for men; among women, however, no predictive value was apparent. CONCLUSION–These results are empirical evidence for the intuitive opinion among doctors that a curved, upward sloping ST segment, resulting in slight ST elevation at 80 ms, indicates low risk compared with the isoelectric flat, stretched ST segment.